Management of African root and tuber scale using improved cassava genotypes and mineral fertilizers - Lema, K.M.; Tata-Hangy, K.W.; Bidiaka, M. (2004)
The African root and tuber scale (ARTS), Stictococcus vayssierei Richard, is an insect species indigenous to Africa, which has recently become an economic pest of cassava (Manihot esculenta Crantz) in many parts of the Democratic Republic of the Congo (D R C). This scale infests underground parts of the plants and prevents young plants from tuberising, thus, causing yield losses of up to 100%. In order to evaluate control components that can be combined into an effective strategy for the management of the scale, six improved cassava genotypes were evaluated for resistance against the scale and NPK fertiliser was tested at the recommended rate as a pest control component. The fertiliser application was made as basal dressing and on one improved clone (F100) with a local variety. Results indicated that ARTS infestations were delayed on ‘Kinuani', F100 and the local clone, ‘Kileba', as no scales were observed on them 6 months after planting (MAP). The sweetest improved genotype, ‘Papayi', harboured the highest number (134.8 insects plant-1) of scales. At 9 and 12 (harvest) MAP, all clones were relatively highly infested, except for the bitter genotype, ‘Sadisa'. This clone also yielded more than the local clone. Mineral fertiliser application significantly increased scale population density on F100, and plant height on both F100 and the local clone. It did not significantly affect the number of tuberous roots and root yield on either the improved F100 or on ‘Kileba'.